2019
DOI: 10.1109/access.2019.2945404
|View full text |Cite
|
Sign up to set email alerts
|

Music for Sleep and Wake-Up: An Empirical Study

Abstract: In this paper, we present our study on investigating the effect of music for sleep induction and wake-up. Unlike existing studies that mostly focused on understanding how specific types of music affect sleep for insomnia patients or older people in laboratory conditions, we aim to study the effect of pop music with respect to the musical features on both sleep and wake-up of young adults without serious sleep disorder in the real-world environment. We conduct two extensive experiments, for which we carefully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Several studies have reported that listening to music alleviates sleep disturbance problems, including insomnia. It has been reported that listening to music reduces heart rate, blood pressure, and respiration rate and even reduces activity of the sympathetic nervous system [ 47 ]. To induce sleep, we primarily use slow, repetitive rhythms, which create a sense of safety and security that can prepare and elicit a sleep response in the brain [ 48 ].…”
Section: Musicmentioning
confidence: 99%
“…Several studies have reported that listening to music alleviates sleep disturbance problems, including insomnia. It has been reported that listening to music reduces heart rate, blood pressure, and respiration rate and even reduces activity of the sympathetic nervous system [ 47 ]. To induce sleep, we primarily use slow, repetitive rhythms, which create a sense of safety and security that can prepare and elicit a sleep response in the brain [ 48 ].…”
Section: Musicmentioning
confidence: 99%
“…In agreement, music can affect work efficiency and people's sleep quality if they choose the music they prefer. Ami [6] investigated how prescribed and preferred music influences sleep quality [7]. Their results showed no significant difference between the prescribed and preferred music groups.…”
Section: Introductionmentioning
confidence: 99%